Misperceived Social Norms and Willingness to Act Against Climate Change - Andre, Peter; Boneva, Teodora; Chopra, Felix; Falk, Armin (The Review of Economics and Statistics, 2024)
Abstract We document the individual willingness to act against climate change and study the role of social norms in a large sample of US adults. Individual beliefs about social norms positively predict pro-climate donations, comparable in strength to universal moral values and economic preferences. However, we document systematic misperceptions of social norms. Respondents vastly underestimate the prevalence of climate-friendly behaviors and norms. Correcting these misperceptions in an experiment causally raises individual willingness to act against climate change and individual support for climate policies. The effects are strongest for individuals who are skeptical about the existence and threat of global warming.